THE N:K RATIO IN CHERNOZEM AND CROPS UNDER DIFFERENT FERTILISATION PRACTICES AND CLIMATE CHANGE - Miroshnychenko, Mykola; Hladkikh, Yevheniia; Volosheniuk, Olesia; Khristenko, Anatoly (Journal of Agricultural Sciences (Belgrade), 2026)
Despite nutrient stoichiometry is widely applied to assess plant nutrition, agronomists in Ukraine traditionally use absolute test values. To address this gap, the temporal variability of the N:K ratio in soil and plant tissues was considered in a long-term field experiment (1971–2017) investigating the effects of different potassium fertilisation systems on crop rotation productivity in the northeastern Ukraine (Kharkiv region). The study compared the aftereffect of a high potassium background (1800 kg ha⁻¹) and the systematic application of mineral fertilisers (NPK) at single and double rates within the crop rotation. Available K in Chernozem was positively correlated with annual precipitation, influencing the stoichiometric balance in plant tissues. Under dry conditions, the N:K ratio narrowed significantly, particularly with potassium-only fertilisation. In contrast, balanced NPK application maintained an N:K ratio comparable to that observed under optimal moisture conditions. The relationship between available K and water highlights the need to use stoichiometric relationships, including the N:K ratio, for balanced plant nutrition in the context of climate change. Overall, potassium fertilisation enhanced crop rotation productivity and contributed to a more stable nutrient ratio balance.